Engaged Pedagogy and Transformative Learning in Graduate Education: A Service Learning Case Study - Levkoe, Charles; Brail, Shauna; Daniere, Amrita (Canadian Journal of Higher Education, 2014)
Operating at the interface between ideas and action, graduate education in geography and planning has a responsibility to provide students with theoretical and practical training. This paper describes service-learning as a form of engaged pedagogy, exploring its ability to interrogate notions related to the “professional turn” and its contributions to transformative learning. Using a case study of a graduate-level service-learning course at the University of Toronto, we address the challenges associated with service-learning and highlight opportunities for students, faculty, universities, and community organizations. Our case study is based on assessment and analysis of the course and contributions to student learning, professional development, and community engagement. We contend that, at the graduate level, service-learning is an underutilized pedagogical tool. Service-learning can impart high-demand skills to graduate students by transforming how students learn and move from knowledge into ideas and ultimately action, and by offering opportunities for developing higher-order reasoning and critical thinking.